2016
DOI: 10.1002/slct.201600422
|View full text |Cite
|
Sign up to set email alerts
|

The Stability and Structural, Electronic and Topological Properties of Covellite (001) Surfaces.

Abstract: Covellite (CuS) is a transition metal chalcogenide mineral, its structure can be described as a succession of planar CuS layers and Cu2S2 double layers. The success of the synthesis of the covellite nanoparticles enhanced their properties with potential applications in energy production and catalysis. Furthermore, covellite is involved in reactions of environmental importance and in the hydrometallurgical process for copper extraction. Investigations of the surface properties with relaxation/reconstruction are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 71 publications
2
19
0
Order By: Relevance
“…The CuS (001) surfaces in this study were cleaved from the CuS unit cell optimized in our previous study . The optimized lattice parameters are a = b = 3.8045 Å and c = 16.496 Å, which are in good agreement with other reported theoretical data . All surface structures in this study were modeled with the p (3 × 3) supercell.…”
Section: Computational Detailssupporting
confidence: 74%
See 1 more Smart Citation
“…The CuS (001) surfaces in this study were cleaved from the CuS unit cell optimized in our previous study . The optimized lattice parameters are a = b = 3.8045 Å and c = 16.496 Å, which are in good agreement with other reported theoretical data . All surface structures in this study were modeled with the p (3 × 3) supercell.…”
Section: Computational Detailssupporting
confidence: 74%
“…The understanding of CuS surfaces is also far from clear. With a hexagonal crystal structure, most studies focus on the (001) surface of CuS using stoichiometric models, , while the defects, which are known to be very important on surfaces and nanomaterials, have not been studied in detail yet. These deficiencies in basic understanding of covellite created a huge gap between experimental and theoretical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the PDOS showed that both Cu 3d (Figure S12c,d) and S 3p (Figure S12e,f) had the high occupation action before and after contact. As shown in Figure S12g–j, both S p z and Cu d z 2 peaks were obvious and exhibited similar shape, suggesting the coupling between S p z and Cu d z 2 …”
Section: Resultsmentioning
confidence: 99%
“…. 29 Antibacterial Assay In Vitro. Two kinds of typical pathogenic bacteria (S. aureus and E. coli) were applied to the antibacterial assay.…”
mentioning
confidence: 98%
“…The high crystallinity of the deposited films could be attributed to the slow but continuous ionic layer‐by‐layer deposition that takes place in SILAR, also supported by a suitable matching between the different deposited ionic layers and the substrate structure, allowing reaching better order among the deposited species. The crystalline structure of covellite has been described as composed of successive planar layers of Cu atoms bonded to S atoms, with different coordination environments, and the SILAR process could be naturally favoring this layer by layer structure. Nevertheless, this observation requires deeper studies focused on the growth mechanism, which is beyond the scope of this work.…”
Section: Resultsmentioning
confidence: 99%